Biodegradable silk fibroin-based bio-piezoelectric/triboelectric nanogenerators as self-powered electronic devices. (1st June 2022) - Niu, Qianqian; Wei, Haifeng; Hsiao, Benjamin S.; Zhang, Yaopeng
Abstract: Bio-piezoelectric/triboelectric nanogenerators (PENGs/TENGs) are promising components for the next generation of self-powered electronic devices due to their green energy harvesting characteristics, biodegradability, and biocompatibility, which are not fully present in regular PENGs/TENGs. As a natural and abundant biomaterial, silk fibroin (SF) shows great potential for fabricating bio-PENGs/TENGs. In this review, the working principles of typical SF-based bio-PENGs/TENGs are summarized. The latest advances in partially and fully biodegradable SF-based bio-PENGs/TENGs are highlighted, focusing on aspects including their molding structures, performance, working mechanisms, and application scenarios. Challenges including output performance, achieving full biodegradability, encapsulation structure, and biosafety are also described. These SF-based bio-PENGs/TENGs show great potential for emerging energy and electronic applications, as well as for in vitro / in vivo biomedicine. Graphical Abstract: ga1 Highlights: The advances of partially and fully biodegradable silk fibroin (SF)-based PENGs/TENGs were reviewed. The molding structures, performance, working mechanisms, and application scenarios of SF-based PENGs/TENGs were presented. The challenges and future perspectives of SF-based PENGs/TENGs were discussed.